Vamos a Ojo de Agua - Hernández, Gabriela (2013)
Spaces and dynamics of popular recreation that are disappearing in Costa Rica: oral memory of the public baths of Ojo de Agua in the province of Heredia. The objective is to show how the model of neo-liberal development, applied in the country as from the 1980’s, and the adoption of globalized lifestyles affect the popular sectors and cultures, their expressions and diversity, and how these ingeniously find ways to reinvent and survive.